The Increase of the size of the shadow economy of 18 OECD countries: Some preliminary explanations - Friedrich Schneider (Johannes Kepler University of Linz, Department of Economics, 2000)
The latest empirical results of the size of the shadow economy in 18 OECD countries are presented, using the currency demand approach to calculate the shadow economy over time. The results indicate a strong increase in the size of the shadow economy, over the period 1960 to 1998 and for 15 of the 18 investigated OECD-countries the size of the shadow economy is more than 13 % of the GNP for the year 1998. Also an analysis is given about the size of influences of major causes (direct and indirect tax burden and government regulation) on the shadow economy for Austria.
Keywords: H23; H26; H29; 330; Schattenwirtschaft; Steuerbelastung; Regulierung; Österreich; OECD-Staaten